COVID-19 and ophthalmology: role of the immune system - Acosta-Viera, Alvaro (2020)
COVID-19 causes various clinical manifestations, ophthalmological manifestations present as viral conjunctivitis. After the entry of the virus, it will produce complex immune response routes, receptors for the virus are found in cells of the ocular surface, therefore it could give a local infection, it is likely that after the entry of the virus, a limited response of ocular inflammation, which could be mediated by the immune privilege approach.